2021
DOI: 10.1183/13993003.01694-2021
|View full text |Cite
|
Sign up to set email alerts
|

Selexipag for the treatment of chronic thromboembolic pulmonary hypertension

Abstract: Treatment options for inoperable chronic thromboembolic pulmonary hypertension (CTEPH) remain limited. Selexipag, an oral selective IP prostacyclin-receptor agonist approved for pulmonary arterial hypertension, is a potential treatment option for CTEPH.In this multicentre, randomised, double-blind, placebo-controlled study, 78 Japanese patients with inoperable CTEPH or persistent/recurrent pulmonary hypertension after pulmonary endarterectomy and/or balloon pulmonary angioplasty were randomly assigned to recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 27 publications
(51 reference statements)
0
38
0
Order By: Relevance
“… 1 The treatment strategy has been extended recently to anticoagulation, pulmonary vasodilators (riociguat and selexipag), BPA, and PEA. 1 , 4 , 5 These current advances provide a good prognosis, and the 5‐year survival rate is 92.0%, which is extremely good compared to those of other types of PH. 3 Generally, this disease has a chronic course; however, in some cases, the condition of the patient deteriorates, as in our case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 The treatment strategy has been extended recently to anticoagulation, pulmonary vasodilators (riociguat and selexipag), BPA, and PEA. 1 , 4 , 5 These current advances provide a good prognosis, and the 5‐year survival rate is 92.0%, which is extremely good compared to those of other types of PH. 3 Generally, this disease has a chronic course; however, in some cases, the condition of the patient deteriorates, as in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic thromboembolic pulmonary hypertension is defined as Group 4 PH 1 . The treatment strategy has been extended recently to anticoagulation, pulmonary vasodilators (riociguat and selexipag), BPA, and PEA 1,4,5 . These current advances provide a good prognosis, and the 5‐year survival rate is 92.0%, which is extremely good compared to those of other types of PH 3 .…”
Section: Discussionmentioning
confidence: 99%
“… 94 The CTREPH trial 95 also demonstrated significant improvement in 6MWD with high‐dose subcutaneous treprostinil in inoperable CTEPH. Selexipag has also been shown to reduce PVR in patients with CTEPH in a small RCT, leading to its approval for this condition in Japan 96 ; however, a larger study—the SELECT study (NCT03689244) was stopped early due to futility so utility in this condition is unclear.…”
Section: Cteph: Updates On Diagnosis and Management Dr Nick Kimmentioning
confidence: 99%
“…Selexipag was reported to be effective for CTEPH. 1 In Japan, it has been approved for CTEPH since August 2021. The patient’s PAP was significantly high; therefore, we initiated combination therapy of riociguat and selexipag.…”
Section: Case Descriptionmentioning
confidence: 99%